Finland : Financial Sector Assessment Program: Technical Note-Contingency Planning and Crisis Management. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for Finland in the area of contingency planning and crisis management (CPCM). Finland's CPCM framework rests on a strong foundation. In addition to the new European Union framework, Finland can build on a cooperative culture among its financial oversight agencies, which can help in times of crisis. Furthermore, the Finnish financial oversight architecture ensures the functional separation of potentially conflicting CPCM responsibilities: supervision, resolution, and emergency liquidity support. The clear separation of functions also helps crisis preparedness. Moreover, Finland also has a strong tradition of testing systemwide operational risks.